Bird diversity in the coastal forest area of Tabanio developed to popular scientific book for students' critical thinking ability: The practicality test - Nur Abdi Suga; Dharmono Dharmono; Muhammad Zaini (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
The main problem experienced by educators is the lack of innovation in teaching materials that can facilitate students and increase learning motivation in understanding a material so that it is necessary to develop innovative teaching materials, one of which is popular scientific books (BIP). This development research went through several tests such as the practicality of BIP bird species diversity in the Tabanio coastal forest area so that BIP development was obtained which could train students' critical thinking skills. The development stages include self-evaluation, expert test, individual test, small group test, field test. However, this research is limited to practicality tests only. The types of data are descriptive data, using readability instruments, BIP implementation and student responses are used for practicality of content, practicality of expectations and actual. The results showed that the Popular Scientific Book on the Diversity of Bird Species that had been developed was stated to be very practical based on the BIP individual test which was stated to be very good with an average of 83.59%. The Popular Scientific Book on Bird Species Diversity that has been developed is declared practical because the results of student responses with an average score of 92.30% with very good criteria, results of BIP implementation on average 83.33% with criteria strongly agree. Based on this, the developed BIP is very practical to use and makes it easier for students to learn.Abstrak Permasalahan utama yang dialami oleh pendidik yaitu kurangnya inovasi bahan ajar yang dapat memudahkan mahasiswa dan menambah motivasi belajar dalam memahami suatu materi sehingga perlu adanya pengembangan sutau bahan ajar yang inovatif salah satunya yaitu buku ilmiah populer (BIP). Penelitian pengembangan ini didapatkan melalui beberapa uji seperti kepraktisan BIP keanekaragaman jenis burung di kawasan hutan pantai Tabanio sehingga didapatkan pengembangan BIP yang dapat melatih kemampuan berpikir kritis mahasiswa. Tahap-tahap pengembangan meliputi evaluasi diri, uji pakar, uji perorangan, uji kelompok kecil, dan uji lapangan. Akan tetapi, penelitian ini dibatasi hanya uji kepraktisan. Jenis data yaitu data deskriptif, menggunakan instrument instrumen keterbacaan, keterlaksanaan BIP dan respon mahasiswa digunakan untuk kepraktisan isi, kepraktisan harapan dan aktual. Hasil penelitian menunjukan buku ilmiah populer Keanekaragaman Jenis Burung yang telah dikembangkan dinyatakan sangat praktis berdasarkan uji perorangan BIP ini dinyatakan sangat baik dengan rata-rata 83,59%. Buku Ilmiah Populer Keanekaragaman Jenis Burung yang telah dikembangkan dinyatakan praktis karena hasil respon mahasiswa dengan rata-rata nilai 92,30% dengan kriteria sangat baik, hasil keterlaksanaan BIP rata-rata 83,33% dengan kriteria sangat setuju. Berdasarkan hal tersebut BIP yang dikembangkan sangat praktis digunakan dan memudahkan mahasiswa dalam pembelajaran.